Os desafios do uso da resina de PET reciclado na indústria de alimentos e bebidas - Uchida, Cintia Narumi (Universidade Federal de São Carlos, 2021)
PET, as well as many other plastics nowadays, has presented great interest in study, especially regarding its recycling. The polymeric residues discarded incorrectly in the environment have generated a negative impact. When disposed of in nature, the plastic can be transformed into microplastics that pollutes the environment and can be toxic to animals. As a solution to this problem, several companies have invested their efforts in the reuse of these materials. Poly(ethylene terephthalate), presents among many aspects the advantage of being a light material, with good mechanical and optical properties, and stands out for having gas barriers such as CO2 and O2. Thus, the material has become very attractive for bottles and food packaging, which are the largest applications of PET. In order to make the packaging industry less damaging to the environment and to generate a circular economy, research has been developed to enable the use of rPET for food applications. However, some challenges such as the presence of contaminants, decreased optical and mechanical properties, and the change in the intrinsic viscosity of the material may be barriers that make this use difficult. Thus, this study had as its main objective, to analyze practical research from different authors for the influence of these parameters on the final recycled material.
The challenges of using recycled PET resin in the food and beverage industry
Keywords: PET; Reciclagem; PET-PCR; Embalagens; Garrafas; Propriedades; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES